Flor Revisited (Again): eQTL and Mutational Analysis of NB-LRR Mediated Immunity to Powdery Mildew in Barley - Roger Wise; Priyanka Surana; Greg Fuerst; Ruo Xu; Divya Mistry; Julie Dickerson; Dan Nettleton (Journal of Integrative Agriculture, 2014)
Genes encoding early signaling events in pathogen defense often are identified only by their phenotype. Such genes involved in barley-powdery mildew interactions include Mla, specifying race-specific resistance; Rar1 (Required for Mla12-specified resistance1), and Rom1 (Restoration of Mla-specified resistance1). The HSP90-SGT1-RAR1 complex appears to function as chaperone in MLA-specified resistance, however, much remains to be discovered regarding the precise signaling underlying plant immunity. Genetic analyses of fast-neutron mutants derived from CI 16151 (Mla6) uncovered a novel locus, designated Rar3 (Required for Mla6-specified resistance3). Rar3 segregates independent of Mla6 and Rar1, and rar3 mutants are susceptible to Blumeria graminis f. sp. hordei (Bgh) isolate 5874 (AVRa6), whereas, wild-type progenitor plants are resistant. Comparative expression analyses of the rar3 mutant vs. its wild-type progenitor were conducted via Barley1 GeneChip and GAIIx paired-end RNA-Seq. Whereas Rar1 affects transcription of relatively few genes; Rar3 appears to influence thousands, notably in genes controlling ATP binding, catalytic activity, transcription, and phosphorylation; possibly membrane bound or in the nucleus. eQTL analysis of a segregating doubled haploid population identified over two-thousand genes as being regulated by Mla (q value/FDR=0.00001), a subset of which are significant in Rar3 interactions. The intersection of datasets derived from mla-loss-of-function mutants, Mla-associated eQTL, and rar3-mediated transcriptome reprogramming are narrowing the focus on essential genes required for Mla-specified immunity.